The Daily Sun subscribers - Mahe, Xolani (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis comprises interlinked short stories, verfabula, sketches, fragments, flash fiction, folktales, anecdotes, and the epistolary form. I write in English tinged with IsiXhosa. In terms of specific influences, the collection is strongly influenced by the experimental writing of Kathy Acker and Samuel Delany notably the uncompromising ways in which they contort formal grammar and sexuality, the defamiliarizing function of the phantasmagoria in the films of Alejandro Jodorowsky and David Lynch, the techniques of the picturesque as used by Amos Tutuola, and, importantly, narration in the present tense as deployed in Dambudzo Marechera's House of Hunger which results in negation and subversion of the narrative depiction of the past, the present, and the future. On the stylistic level, I am strongly influenced by the haunting surrealism of Sony Labou Tansi, the eccentric meditations of Julio CortÃ¡zar, and the iconoclastic rants of Lesego Rampolokeng.
Keywords: Creative writing (Higher education) -- South Africa; Diaries -- Authorship; Books Reviews; South African fiction (English) 21st century; Short stories, South African (English) 21st century